Implementing Cascade Classifier In Android Application “Find Marks” - R.B Wahyu; Hidayat Saputra (President University, 2018)
Nowadays going through other places is easier to do. Explore new area is quite common activities by every people since they have sense to know about the environment or situation around them or just curiosity about somewhere else they didn’t know yet. People have different ability to adapt and ways to know how the environment around them. Not all people feeling easy with their new environment and socialize with local people.This research intends to implement object detection as one of feature from computer vision in android application. This application also will assist users how to training image for cascade classifier. User will be able to do object detection using built in Android smartphone camera to receive direction to some place or building from provided marker or logo. It also gives user information about the current place.